Implementasi Perjanjian Kerja Dalam Penempatan Tenaga Kerja Indonesia Ke Luar Negeri - Meita Djohan Oelangan (Law Faculty of Universitas Bandar Lampung, 2014)
Indonesia workforce placement to foreign countries is an effort to realize equal rights and opportunities to have proper job and income, and the conduct of workforce placement should consider human prides, human rights, legal protections, even distributions of job opportunities, and workforce providing according to national needs. The implementation of employment contract for Indonesian workforce placement to foreign countries was not optimal because many PPTKIS violated the employment contract in conducting Indonesian workforce placement to foreign countries. The employment contract violation were both in procedural and substance matters. The cause of employment contract violations were low education level of Indonesian workforce especially those who worked for family servants, the workforce was not selectively recruited, Indonesia workforce employersâ behaviors did not respect their employeesâ rights, and government regulations did not represent the Indonesian workforce interests, especially in family servant job sector.